Influência da terapia laser de baixa intencidade em células precursoras miogênicas (in vitro) e durante a regeneração muscular (in vivo) - Amaral, André Capaldo (2004)
The Low Intensity Laser Therapy (LILT) constitutes one of the resources most used by physical therapists, with the goal of stimulating the process of repairing the skeleton muscle tissue. On the other hand, the intense utilization, its respective action mechanisms and therapeutic effectiveness are not scientifically proved. Based on this, we elaborated the present study aiming to investigate the influence of the LILT, at wavelengths (λ) usually used at clinical practices (670, 685 and 830 nm), on the function of the Myogenic Precursor Cells (MPCs), directly responsible for the tissue regeneration process. The beginning phase was carried out throughout in vitro experiments, determining the alterations started by radiations over the proliferation ability and the cellular differentiation. The MPCs used were in the second passage, after had been extracted from four days old Wistar rats. To analyze the proliferation, it was elaborated, for each λ, a dose-response data curve including the control group constituted of non-radiated cells, and the irradiated groups with doses of 0.3; 0.6; 0.9; 1.2; and 1.5 J/cm2. This procedure was carried out with the cells under the influence of 5 or 10% of fetal bovine serum (FBS). The dose demonstrating the highest effectiveness on the cellular proliferation in each radiation, was used to establish the influence on the process of cellular differentiation, and investigated throughout the analysis of the expression of the genes related to the isoforms IIa and IIx of the myosin heavy chain (MHC). The final phase of the study was pointed towards the radiation action evaluation, at the same dose parameters used before, on the muscle regeneration process in vivo, after induced cryoscopy lesion at the Tibialis anterior muscles of adults Wistar rats. There were evaluations of the histological, histochemical aspects for the Succinic Dehydrogenase enzyme (SDH) and the activity of the Lactate Dehydrogenase enzymes (LDH) and Citrate Sintase (CS). The outcomes demonstrated that the radiation at λ of 670, 685 and 830 nm promoted an increase of 56.8, 70.6 and 84.8 % on the proliferate ability of the PMCs. These values were achieved with the 1.2, 0.6 and 0.3 J/cm2 doses respectively, and with the cells under the influence of 5% of FBS. The highest concentration of serum (10% of FBS) determined a less pronounced bio-stimulating effect, rising only 13.6, 17.5 and 10.9 %, respectively. In relation to the MHC isoforms expression rate, it showed that there was a significant fall of the IIa isoform, due to the action of the 685 nm, and an increase of the IIx isoform, due to the action of the 685 and 830 nm radiations, in relation to the non-radiated cells rate. By means of in vivo analysis, it was possible to demonstrate the ability of radiation at λ of 685 and 830 nm on increasing DHL enzymes and CS during the muscle regeneration process. Therefore, according to the outcomes it is allowed to attribute to the LILT an ability λ and dose-dependent of influencing the proliferation function and the metabolism of the MPCs. It was not possible to infer its effect on the cellular differentiation process, because of the inverted effect on the MHC isoforms expression, though.